(3HeYHO OfOQI (B[U] (3GdbGYI (B: s (3OQGSI dZhjI MVGQjI (B/ s - (3gHI CHhGdMLGL eMeO YHOGdcQjes; (3eMeO QLH SjO (B: s; (3hLOi QeVGf eMeO (B: s ((3GdefjG (B: s (3gHI CHhGdMLGL eMeO YHOGdcQje (B: s, 2018)
(3jYJHQ eYHO OfOQI hGMOG ef Cge GdeYGHO GdeUQjI GdJi JQLY ddYUQjf GdjhfGfi h GdQheGfi fXQG dLhOI MaXI h deG JMhjg LOGQJg GdNGQLjI h GdOGNdjI ef efGXQ YOjOI bjeI h fUhU gGeI JhVM GdcKjQ ef GdeYJbOGJ GdOjfjI dgPG GdYUQ gPG HGdEVGaI Gdi eG jMJhjg ef SQGOjH JYO ef CTgQ h Cge GdSQGOjH GdedMbI HGdeYGHO fXQG dJfXjegG h deG JJVefg ef fbhT QGFYI h fUhU RGNQI HGdeYdheGJ GdbjeI(B. (3h WHbG dPdc abO Je ENJHGQ ehVhY GdbGYI (B((3jh(B) ((3ES EJT(B-(3Ef Ji CQ(B) (3HGdeYHO ddHMK h GdOQGSI(B: (3h ai SHjd GdJYQa Ydi OhQ GdbGYI abO bGeJ GdWGdHI HJQLeI cd fUhU GdbGYI h OQGSJgG Ydi fMh hGVM(B: (3Gdi LGfH OQGSI GdeYfi GdQeRi h GdOjfi dcd efGXQ GdJbOeGJ h GdWbhS GdOjfjI GdJi hQOJ Ydi LOQGf GdbGYI(B: (3h bO GYJeOJ GdWGdHI Ydi CMOK fTQ Ydei deJf GdfUhU h GdefGXQ GdNGUI HGdOQGSI GdMGdjI h gh GdLRA GdSGHY ef fTQ eYHO OfOQIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdefjG (B- (3cdjI GdBOGH (B- (3bSe GdBKGQ GdeUQjIs
Keywords: (3EjRjS s; (3MJMhQ s; (3OfOQg s